Epidemiological profile of american tegumentary leishmaniasis in the state of Maranhão in recent years - Silva Farias, Francisco Jhon Anderson; do Ceu da Silva, Edigleison; Angelo da Silva, Suzana; Soares Pinheiro, Valéria Cristina; Trindade Bezerra, Juliana Maria (Revista Multidisciplinar em Saúde, 2021)
Introduction: American Tegumentary Leishmaniasis (ATL) is a non-contagious disease, caused by a protozoan of the genus Leishmania, vector-borne by sandflies. Initially it is enzootic, but it can affect humans in a secondary way, characterizing itself as a zoonosis. It has great epidemiological importance due to the complexity of the treatment. The disease has been spreading on a large scale throughout Brazil, as well as in the state of Maranhão. Methods: This study is a descriptive approach with the use of confirmed cases of ATL by the Department of Informatics of the Unified Health System, for the years 2010 to 2019 for the state of Maranhão. The following variables were analyzed: annual notifications, gender, age group, clinical forms, case outcome and municipalities with the most notifications. Results: During the study period, 19,043 cases were confirmed in the State. The year 2011 had the highest number of notifications, with 2,948 cases and an incidence of 44.83 cases per 100,000 inhabitants. The male gender was the most affected with 71.9%. The predominant age group was between 20 and 39 years old, with 42.7%. The cutaneous form was prevalent with 96.4%. The three municipalities with the highest number of records were Montes Altos (West Mesoregion), Buriticupu (West Mesoregion) and Arame (Centro Maranhense Mesoregion). Conclusions: The state of Maranhão is considered endemic for ATL, so it is considered essential to continuously adopt measures to combat the vector and to conduct educational campaigns that inform the population about minimizing the possibilities of disease transmission.